2023
DOI: 10.1088/1748-9326/acab77
|View full text |Cite
|
Sign up to set email alerts
|

Typicality of the 2021 Western North America summer heatwave

Abstract: Elucidating the statistical properties of extreme meteo-climatic events and capturing the physical processes responsible for their occurrence are key steps for improving our understanding of climate variability and climate change and for better evaluating the associated hazards. It has recently become apparent that large deviation theory is very useful for investigating persistent extreme events, and specifically, for flexibly estimating long return periods and for introducing a notion of dynamical typicality.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 71 publications
5
16
0
Order By: Relevance
“…In the intermediate 15-day case, trajectories including 2021 analogues lead to a much higher probability of reaching or surpassing the event, but 4% of the trajectories are higher even with analogues taken from other years, showing that events of comparable or larger magnitude at this time scale are rare but not impossible in the current climate. This largely supports the very recent findings of Lucarini et al (2023) based on a large deviation analysis. When considering a 15-day temperature average, the authors argued that the 2021 event is an unlikely but possible manifestation of climate variability, whose probability of occurrence is greatly amplified by the ongoing climate change.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the intermediate 15-day case, trajectories including 2021 analogues lead to a much higher probability of reaching or surpassing the event, but 4% of the trajectories are higher even with analogues taken from other years, showing that events of comparable or larger magnitude at this time scale are rare but not impossible in the current climate. This largely supports the very recent findings of Lucarini et al (2023) based on a large deviation analysis. When considering a 15-day temperature average, the authors argued that the 2021 event is an unlikely but possible manifestation of climate variability, whose probability of occurrence is greatly amplified by the ongoing climate change.…”
Section: Discussionsupporting
confidence: 91%
“…Extreme value and large deviation analyses have shown that human-induced global warming has increased both the likelihood and the intensity of this heatwave (Philip et al, 2021;Lucarini et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…These findings can enrich our understanding of the 2021 WNA heatwave and help countries in this region to make appropriate adaptation measures to future climate change to a certain degree. Finally, previous studies indicated that some specific synoptic conditions with amplified ridge, offshore/downsloping flow, and regional soil moisture deficiency amplified the 2021 heatwave in cities over WNA (Bartusek et al., 2022; Lucarini et al., 2022; Neal et al., 2022; Qian et al., 2022). However, it is unclear with confidence whether these conditions associated with the 2021 WNA heatwave will be enhanced accordingly in the future, which deserves further study.…”
Section: Conclusion and Discussionmentioning
confidence: 90%
“…The findings of this study are basically consistent with those reported in recent studies (i.e., Philip et al., 2021; McKinnon & Simpson, 2022; Thompson et al., 2022) that a higher occurrence likelihood of future heatwave similar to the 2021 one is expected over WNA in a warmer world. In these studies, the conclusions are primarily based on the analysis of one state‐of‐the‐art earth system model (i.e., Lucarini et al., 2022; McKinnon & Simpson, 2022; Terray, 2022; Thompson et al., 2022) or a specific warming scenario (i.e., Philip et al., 2021; Bartusek et al., 2022). As such, these approaches may not fully quantify future prospects of a heatwave similar to that observed in 2021 over WNA, considering the possible biases of a single climate model and the divergent possibilities of future trajectories.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Western North America (WNA), including parts of Canada and the US, experienced an unprecedented temperature extreme in late June to early July 2021 that broke historical records (Bartusek et al., 2022; Bercos‐Hickey et al., 2022; Dong et al., 2023; Heeter et al., 2023; Lin et al., 2022; Loikith & Kalashnikov, 2023; Lucarini et al., 2023; McKinnon & Simpson, 2022; Qian et al., 2022; Thompson et al., 2022; White et al., 2023). For example, Lytton in British Columbia set a new Canadian record of 49.6°C (ECCC, 2021) and Hanford in Washington state set a new state record of 48.98°C (Loikith & Kalashnikov, 2023).…”
Section: Introductionmentioning
confidence: 97%